Recent Advances in the Diagnosis and Management of Plant Diseases - Awasthi, L.P (Springer India : Imprint: Springer, 2015)
This book is a compilation of the most challenging and significant chapters on the diagnosis and management of important bacterial, fungal, viral, viroid, phytoplasma, non parasitic diseases and various physiological disorders, in various crops. The chapters have been contributed by eminent plant pathologists, having wide experience of teaching and research on various crops with different types of diseases, which cause great economic losses. The book would be very useful for students, teachers and researchers of plant pathology. This book highlights recent advances made in the development of new types of resistance in host plants and alternative strategies for managing plant diseases to improve food quality and reduce the negative public health impact associated with plant diseases. Having entered into 21st century advancements in the Diagnosis of Plant Pathogens and Plant Disease Management need to be closely examined and adequately applied, so that newer challenges facing plant pathology could be adequately addressed in attaining food security for the growing population.   Substantial advancements have been made in terms of expanding knowledge base of the biology of plant-microbial interactions, disease management strategies and application and practice of Plant Pathology.  Application of molecular biology in Plant Pathology has greatly improved our ability to detect plant pathogens and in increasing our understanding, their ecology and epidemiology. Similarly, new technologies and resources have been evolved for the development of sustainable crop protection systems by different control strategies against various pests and pathogens that are important components of the integrated pest management programme. Natural products and chemical compounds discovered as a result of basic research and molecular mechanisms of pathogenesis have led to the development of "biorational" pesticides. Biological control has been found to be the most significant approach to plant health management during the twentieth century and promises using modern biotechnology, to be even more significant in the twenty-first century.